Bering-Chukchi-Beaufort Seas bowhead whale (Balaena mysticetus) abundance estimate from the 2019 ice-based survey - Givens, Geof; George, J. Craig; Suydam, Robert; Tudor, Barbara (J. Cetacean Res. Manage., 2021)
An ice-based visual survey of the Bering-Chukchi-Beaufort Seas stock of bowhead whales (Balaena mysticetus) was conducted in spring 2019 near Utqiaġvik (formerly Barrow), Alaska. A Horvitz-Thompson-type estimator is used to estimate population abundance from the resulting data, correcting for detection probabilities, whale availability within visual range, and whale passage during periods of missed effort. Analytical methods mirror those used by Givens et al. (2016) for the 2011 survey as much as possible; however, unlike 2011, no simultaneous acoustic monitoring was conducted in 2019, so the availability correction factor had to be estimated from past years. The estimated abundance was 12,505 with 95% confidence interval of (7,994, 19,560) and a CV of 0.228. This estimated abundance is markedly lower than the 2011 estimate of 16,820, but the 2019 confidence interval wholly encompasses the 2011 interval. We do not interpret this finding as evidence of a decline for many reasons including: highly unusual ice conditions, an unusual migration route that was sometimes too distant from observers to detect whales, failure to conduct watch because of closed leads during the early weeks of the migration when numerous whales likely passed, an unusually short perch, and hunters’ heavy use of powered skiffs near the observation perch which likely disturbed the whales during the survey. Furthermore, bowhead health assessment information for 2019 suggests that harvested bowheads did not exhibit obvious reductions in health condition, and aerial surveys in summer 2019 indicated high calf production (Stimmelmayr et al. 2020). Despite the challenges of the 2019 survey, the estimate is adequate for use with the International Whaling Commission’s management procedure and complies with the survey requirements of the Aboriginal Whaling Scheme.